Crafting the Future of Macro Practice. Issue 4 (8th August 2019) - Tropman, John; McBeath, Bowen
ABSTRACT: This Discussion of the Special Issue addresses four interlocking questions of importance for social work macro practice: (1) What is the trajectory of macro practice in schools of social work?; (2) What should be included in a 21st century macro practice curriculum?; (3) How can schools of social work promote research on organizations, managers, and leaders; and (4) What under-explored research topics in organizational and management practice exist? The Discussion links major themes among the 10 commentaries comprising the Special Issue in order to provide some perspective on longstanding concerns to social work scholars. In essence, we transition from a discussion of the commentaries, to situating the concerns of the commentaries in the social work academy. Our central argument is that calls for a strengthening of social work macro practice education and research should be directed at deans and directors. Yet deans of schools of social work are middle managers within complex academic institutional hierarchies. They must regularly compete and collaborate with other deans for resources, interest, and status. Thus, it is incumbent upon macro practice educators and researchers to clearly demonstrate what macro practice education and research do for schools of social work vis-à-vis other professional schools and universities. If macro practice professors cannot argue convincingly and succinctly for their investments in more public fora, then deans and directors may not either. Our argument holds for academic innovators in competitive knowledge industries as much as it does for social entrepreneurs and organizational leaders in competitive human service industries.